Production Modes, Marx’s Method and the Feasible Revolution - Jossa, Bruno (European Scientific Journal, ESJ, 2016)
In Marx, the production mode is defined as a social organisation mode which is typified by one dominant production model which confers significance on the system at large. The prominence of production modes in his overall approach provides clues to the identification of the correct scientific method of Marxism and, probably, of Marx himself. The main aim of this paper is to define this method and to discuss a type of socialist revolution which appears feasible in this day and age.